An ethical view on international trade agreements TTIP and CETA in the Republic of Croatia - Marinčić, Mile (Array, 2019)
The topic of TTIP and CETA was almost completely suppressed in Croatia.1 Those are very important international agreements which could have far-reaching consequences both for the world and individual countries. Maybe Croatia, as well as the EU, is not so much involved in the whole story concerning TTIP. However, CETA is an agreement signed by Canada with the European Union. Therefore, after the approval of the European Parliament, EU provisions, such as the customs policy, can immediately start to apply, which means abolishing duty rates for 99% of the products as early as 1 January 2017. The decision on the CETA conclusion on behalf of Croatia was initiated by the technical Government of Tihomir Orešković at its last session.2 The superficial interpretation of these certainly not harmless agreements is of too little interest to both philosophers and theologians in Croatia, and except for the Centre of Excellence for Integrative Bioethics’3 reaction concerning this question, other philosophical-theological discussions seem to be lacking. The impression is that philosophers and theologians feel these issues do not concern them. In this paper we will try to make clear that the above-mentioned international agreements concern both philosophers and theologians, and that they certainly should, from their field, from the theoretical level, engage in the discussion of the said agreements.